What ails broadband?. - Cooper, M.
Consumers are offered technology for the sake of technology instead of real services. Do people really want broadband Internet access in their homes? It has been five years since household broadband Internet connections first became available. Yet only 4 percent of US homes with Internet-capable PCs have a broadband connection. In Europe, the figure is a paltry 4 percent. Why would not everyone want broadband? It delivers bits at blinding speeds and it will improve our lives in countless ways. We know that because the "techies" have told us so. And that is the problem. Most people do not care about bits per second, packet switching, and latency. They care about how the technology is going to specifically affect their lives-for the better, hopefully. It is the techies who love technology for its own sake, and they are still running the telecommunications industry, as they have for the past 120 years.
Keywords: Europe; Internet-capable PC; USA; Broadband Internet access; Broadband technology; Household broadband Internet connections; Latency; Packet switching; Telecommunications industry